2019
DOI: 10.1530/rep-18-0414
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal capacity, gut hormones and appetite change during rat pregnancy and lactation

Abstract: Pregnancy and lactation increase maternal appetite and adiposity, which in humans can lead to long-term body mass retention. Previous rat reproduction studies suggest that appetite-inhibiting gut hormone, peptide-YY (PYY), is elevated, despite hyperphagia also that gastrointestinal size increases. The present study characterised changes in orexigenic (appetite-stimulating) ghrelin and anorexigenic (appetite-inhibiting) PYY and glucagon-like peptide-1 (GLP-1), and gastrointestinal architecture during pregnancy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 47 publications
1
22
0
Order By: Relevance
“…a chance finding and not likely to reflect diet-specific outcomes. An increased density of ghrelin-expressing cells is consistent with a recent report in rats, where the density of ghrelin immunopositive cells in the stomach mucosa is increased by ~10% at mid-pregnancy compared to non-pregnant animals and increases by a further ~30% by the day of birth (Johnson et al 2019). We also characterised ghrelin protein expression in the murine placenta.…”
Section: Journal Of Endocrinologysupporting
confidence: 91%
See 1 more Smart Citation
“…a chance finding and not likely to reflect diet-specific outcomes. An increased density of ghrelin-expressing cells is consistent with a recent report in rats, where the density of ghrelin immunopositive cells in the stomach mucosa is increased by ~10% at mid-pregnancy compared to non-pregnant animals and increases by a further ~30% by the day of birth (Johnson et al 2019). We also characterised ghrelin protein expression in the murine placenta.…”
Section: Journal Of Endocrinologysupporting
confidence: 91%
“…However, the reported changes in circulating total and acyl-ghrelin during pregnancy vary between studies. Total ghrelin concentration has been reported as lower compared to non-pregnant levels in humans and as lower or unchanged in pregnant rats (Gualillo et al 2001, Shibata et al 2004, Fuglsang et al 2005, Tham et al 2009, Johnson et al 2019. Conflicting evidence is likewise available regarding changes in acyl-ghrelin, with either elevated or lower concentrations during pregnancy in women (Palik et al 2007, Tham et al 2009) and elevated during late pregnancy in a single study in rats (Szczepankiewicz et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Our own digestive system may be similarly modulated by reproductive cues to affect food intake. In mammals, enteric neurons express sex/reproductive hormone receptors 43 and enteroendocrine hormone levels change during reproduction 3 . We argue that pregnancy and lactation represent an attractive, relatively unexplored physiological adaptation to investigate mechanisms of nutrient intake regulation, organ remodelling and metabolic plasticity: mechanisms that might eventually be leveraged to curb appetite and/or weight gain.…”
Section: Discussionmentioning
confidence: 99%
“…In rodents, at mid-pregnancy, such as on day 10 and 15 of pregnancy, plasma ghrelin was decreased [12,41], while on day 20 [12] and day 23 [41] it was increased compared to non-pregnant rats [12]. Comparison of fasting plasma ghrelin concentrations throughout pregnancy showed a decrease with time, resulting in the lowest ghrelin level by day 18 of pregnancy in one study [73], while in nonfasted rats an increase of circulating ghrelin throughout pregnancy was observed [13]; in both investigations there was a normalization of ghrelin concentration at parturition [73]. Noteworthily, one study showed no change in circulating ghrelin due to pregnancy [74].…”
Section: Pregnancy and Deliverymentioning
confidence: 90%